Effect of resistance stretching on flexibility, power and performance of jump float servefor elite volleyball players - Mahmoud Abdelmohsen, N.; Larion, A. (Science, Movement & Health, 2020)
Objective. As in many other sports, flexibility is very important in volleyball, since the lack of it can complicate the assimilation of the execution techniques or technical elements of that discipline. Resistance stretching focus on match strength with flexibility. This means that you only stretch your muscles as often as you can contract them simultaneously. The active contraction of the muscles in the position of the elongated body helps it become more flexible, stronger and stable. This stretch method also helps protect from injury because the player matches the range of motion with strength. The aim of this investigation was to explore the effect of resistance stretching on flexibility, power and performance of Jump Float Servefor elite volleyball players. Methods. Fourteen elite volleyball players from Elminia club. (experimental group 7 players and control group 7 players). The experimental group were receiving ten-weeks intervention of resistance stretching training program (n = 7). The control group were receiving ten-weeks intervention of traditional training. All data collected before and after the program for the experimental and control groups. The researcher conducted the average in height, weight and age. Results. The results showed significant differences were observed between pre-post-tests for experimental group, and posttests between the experimental and control groups in all parameters of flexibility, power and performance of jump float serve.Conclusion:In conclusion, our data suggest that (10) weeks of training with the resistance stretching could improvement of the flexibility, power and performance of jump float serve for elite volleyball players.